Effects of a leucine-rich diet on body composition during nutritional recovery in rats - Ventrucci, G.; Silva, LGR; Mello, MAR; Marcondes, MCCG (Elsevier B.V., 2004)
OBJECTIVE: Protein malnutrition is characterized by a number of morphologic and physiologic alterations, including intestinal mucosal atrophy and impaired nutrient absorption. Impaired absorption accentuates nutritional deficiency and accelerates body weight loss and changes in body chemistry. Because leucine is a ketogenic and oxidative amino acid and stimulates the protein synthesis, we examined the ability of young rats to recover from protein malnutrition by feeding them a control balanced or a leucine-rich diet for 60 d.METHODS: At the end of the 60-d period, body, liver, and muscle weights; glucose, methionine, and leucine intestinal absorption; and carcass chemical composition were evaluated.RESULTS: Body weight gain was higher in the control balanced and leucine-rich groups than in control rats, indicating that adequate refeeding allows body weight to recover in these groups. Methionine and glucose absorptions were impaired in malnourished rats but were restored after nutritional recovery. The leucine-rich diet resulted in an increase in carcass collagen nitrogen but maintained the carcass structural nitrogen.CONCLUSIONS: These results indicated that leucine supplementation during nutritional recovery from protein malnutrition improves protein carcass restoration. However, the precise mechanism of the leucine effects involved in this response remains to be elucidated.
Keywords: amino acids; body composition; leucine; intestinal absorption; undernourishment